2020
DOI: 10.1002/hed.26432
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes in patients with head and neck cancer treated with concurrent chemoradiation with weekly versus bolus cisplatin

Abstract: Background: Patient Reported Outcome (PRO) data comparing bolus (B-CP) with weekly (W-CP) cisplatin concurrent with radiation are lacking. Methods: We performed a retrospective study comparing PRO among 99 patients with head and neck radiation, 26% who received concurrent B-CP and 73% treated with W-CP. Results: W-CP patients had a higher Charlson comorbidity index (CCI) (P = .004). There were no differences in median cisplatin dose, PROs, percutaneous endoscopic gastrostomy (PEG) dependence or hospitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Considering the patient reported outcomes, Arbab et al [ 9 ] performed a retrospective analysis on 99 patients (73 patients treated with a 1w schedule and 26 with a 3w). Results showed that patients reported outcome resulted to be comparable among the two cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the patient reported outcomes, Arbab et al [ 9 ] performed a retrospective analysis on 99 patients (73 patients treated with a 1w schedule and 26 with a 3w). Results showed that patients reported outcome resulted to be comparable among the two cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It could also reduce chemotherapy-related acute and late side effects, facilitate dose adjustments according to clinical conditions during the treatment and therefore outpatient management, with lower hospitalization rates. Several retrospective and prospective studies [ 6 9 ], as well as different systematic reviews and meta-analysis [ 10 13 ] comparing 1w- and 3w- schedules, showed conflicting and inconclusive results, both in terms of survival outcomes and toxicity profile. Indeed, while most of these studies confirmed that oncologic outcome seems to be similar between the two regimens, hematologic toxicity showed not homogeneous findings among the different analyzed cohort.…”
Section: Introductionmentioning
confidence: 99%
“…JMP Pro version 14.3, SAS Institute, Inc., Cary, NC and SAS 9.4 software, SAS Institute, Inc., Cary, NC were used for subsequent data analyses. Severity of scores were reported as mild (score 1–4), moderate (score 5–6) and severe (7–10) based on the maximum score of symptoms during radiation as per our previous analysis looking at PRO in relation to cisplatin schedule 24 . The association between maximum severity score group and dose to OARs was investigated by using Kruskal–Wallis test.…”
Section: Methodsmentioning
confidence: 99%
“…Severity of scores were reported as mild (score 1-4), moderate (score 5-6) and severe (7)(8)(9)(10) based on the maximum score of symptoms during radiation as per our previous analysis looking at PRO in relation to cisplatin schedule. 24 The association between maximum severity score group and dose to OARs was investigated by using Kruskal-Wallis test. Pearson correlation coefficients were calculated to study the relationship between maximum symptom scores and dose to OARs.…”
Section: Methodsmentioning
confidence: 99%